THE IMPACT OF LIBRARIANS’ INFORMATION LITERACY ON THE QUALITY OF COLLECTIONS IN STATE UNIVERSITY LIBRARIES OF SOUTH KALIMANTAN - Wahdah, Siti; Rahmawati, Laila; Juairiah, Juairiah (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The rapid development of information technology presents significant challenges for libraries in maintaining relevant and accurate collections. Information literacy has become an essential competency for librarians to effectively evaluate, manage, and provide information resources. Purpose: This study examines the relationship between librarians’ information literacy and the quality of library collections in five state universities in South Kalimantan using a quantitative regression approach. Method: All 51 librarians were included through saturated sampling, with data collected via observations, questionnaires, and documentation, and validated for reliability. The findings show that librarians’ information literacy is in the good category (mean 3.20), as is the quality of library collections (mean 3.54). The correlation test produced r = 0.236 (sig. 0.061), indicating a positive yet moderate relationship. Result: These results highlight that stronger information literacy skills contribute to better-managed collections. Conclusion: More broadly, the study suggests that strengthening information literacy competencies can enhance collection development practices not only in South Kalimantan but also in other higher education institutions with similar contexts.